The case against Europe's 2020 agenda - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2010)
The European Union has set out a new strategy for growth and competitiveness. A successor to the Lisbon agenda, the 2020 strategy aims to usher Europe into an era of smart, sustainable and inclusive growth. It is of tremendous importance that Europe speeds up growth. Fiscal stabilization can never be achieved without growth, and many countries in Europe are facing great future challenges to its fiscal policy. However, the 2020 strategy is not going to deliver neither growth nor pro-growth reforms. Like its predecessor, it is a confused strategy with conflicting ambitions. Core areas for policy reforms at the European level are missing in the strategy. In its current form, it will soon be forgotten, if not gone. At the heart of the strategy is a erroneous notion that Europe is such a unified economy that a central strategy works for all countries. Furthermore, it lives and breathes the sort of pop internationalism that presents economic success in other parts of the world as a threat. The current 2020 strategy should be put in the bin. There is no point toying with marginal changes. It is the fundamentals that must change.
Keywords: 330; Wachstumspolitik; Wirtschaftspolitik; Internationale Wirtschaftspolitik; EU-Politik; Kritik; EU-Staaten